Control of mushroom sciarid fly Lycoriella inguena (Dufour) with an azadirachtin-based insecticide - Drobnjaković, Tanja M; Marčić, Dejan; Potočnik, Ivana; Rekanović, Emil; Prijović, Mirjana; Milijašević-Marčić, Svetlana; Stepanović, Miloš (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2019)
The impact of a bioinsecticide based on azadirachtin (Ozoneem trishul 1 %) on the abudance of mushroom flies (Sciaridae: Diptera) was compared to the effect of a commercial formulation of the malathion-based chemical insecticide Etiol tečni. Experiments were conducted in three growing chambers (B6, B7 and B8) of a commercial mushrom farm “Delta Danube” d.o.o., Kovin. Casing treatments were performed in eight replications in a random block design. The azadirachtin-based bioinsecticide was applied in chamber B8 four times (0.5 ml/m2): during casing and later at seven-day intervals. The standard chemical insecticide based on malathion was applied in chambers B6 and B7 twice (2 x 0.3 ml/m2), on the third and sixth day after casing. In all three chambers, the abudance of mushroom flies was monitored by using yellow sticky traps, which were collected weekly and replaced with new ones four times at seven days intervals. The yellow sticky traps were examined in the laboratory under a binocular microscope to determine the presence and density of mushroom flies. Only one species of mushroom fly, Lycoriella ingenua (Dufour), was found on the yellow sticky traps throughout the experimental period. The average number of sciarid flies per mushroom block 15 and 22 days after treatment (DAT) was significantly lower in the test chamber B8 than in chambers B7 and B6, while there was no significant difference 30 and 36 DAT, compared to the control chamber B6. The average number of sciarid flies per mushroom row throughout the experiment was significantly lower in the test chamber B8 than in chambers B6 and B7. The results of our study suggest that the azadirachtin-based bioinsecticide can suppress populations of the mushroom fly L. ingenua and may provide a good alternative to conventional chemical insecticide.
Keywords: mushroom sciarid flies; Lycoriella inguena; Agaricus bisporus; azadirachtin; biopesticides